English as Escape Capital: A Critical Discourse Analysis of English Proficiency in the #KaburAjaDulu Movement on X - Pebrina Nurwahyuningsih; Rahmatillah Rahmatillah (Hasanuddin University, 2026)
This study examines how English proficiency is discussed in the #KaburAjaDulu movement on X in Indonesia. Using Critical Discourse Analysis, the study examines 30 public tweets selected through the X Advanced Search feature with the keyword combinations #KaburAjaDulu and bahasa Inggris, English, IELTS, and TOEFL, filtered to top tweets from 2025 to 2026. Data analysis used Van Dijk's three-dimensional model, namely text structure, socio-cognitive representations, and social context. The results show that English is seen as escape capital, meaning it is viewed less as a means of communication and more as a tool for escaping perceived problems in Indonesia. Three main patterns appear, namely English as a requirement for moving abroad, as an investment in a hoped-for future identity, and as a resource that is not equally available across social classes. The study also identifies contrasting perspectives that emphasize the structural barriers and unequal opportunities faced by many individuals. These results suggest that EFL education in Indonesia should focus more on critical language awareness, as social media shapes learners' perceptions of the value of English.